Ethnobotanical Survey of Plants Used as Memory Enhancer in Three States of Southwestern Nigeria - Olatunji Peter Babawale, Fasola Remi Taiye, Onasanwo Samuel Adetunji (Journal of Applied Pharmaceutical Science, 2016)
This study sought at documenting plants locally used for memory enhancement by the people of three States of Southwestern Nigeria, predominantly inhabited by the Yoruba tribe. A combination of social survey, direct field observations and semi structured questionnaires were administered among the local herb vendors, traditional medicine practitioners (TMPs) and knowledgeable people in plant usage. A total number of 260 respondents were interviewed across the States. The total populations of the respondents were made up of the herbalists (32%), herb sellers (40%) and “other occupation” comprising students and artisans (28%). The total population consisted of 55.4% males and 44.6% females with ages ranging from 10 to 75 years. Thirty seven medicinal plant species belonging to twenty eight families were gathered. Of all the plant species, Bacopa floribunda (R.Br) Wettst and Scoparia dulcis L belonging to the same family Scrophulariaceae had the high ranked of 40 and 27 respectively. A link between plant local names and their usage for memory enhancement was established.
Keywords: Bacopa floribunda, Scoparia dulcis, Scrophulariaceae, Memory enhancement, Medicinal plants.